Eleven new species of Spilogona Schnabl, 1911 (Diptera, Muscidae) from the Altai Mountains of Russia, with key to species - Sorokina, Vera S. (Zootaxa, 2018)
Eleven new Spilogona species: Spilogona altaica sp. nov., Spilogona antoninae sp. nov., Spilogona colorata sp. nov., Spilogona decolorata sp. nov., Spilogona improvisa sp. nov., Spilogona insolita sp. nov., Spilogona longissima sp. nov., Spilogona novgorodovana sp. nov., Spilogona platyfrons sp. nov., Spilogona tanushka sp. nov., Spilogona tara sp. nov. and a key is provided to the 53 species known from the Altai Mountains including 21 species are newly recorded for the Altai, and seven of them also represent new records from Russia: Spilogona meadei (Schnabl, 1915), Spilogona orthosurstyla Xue & Tian, 1988, Spilogona placida (Huckett, 1932), Spilogona setigera (Stein, 1907), Spilogona sororcula (Zetterstedt, 1845), Spilogona spinicosta (Stein, 1907), Spilogona stackelbergi Hennig, 1959). And four species represent new records for the Palaearctic Region: Spilogona flavinervis Huckett, 1965, Spilogona imitatrix (Malloch, 1921), Spilogona nutaka Huckett, 1965, Spilogona incerta Huckett, 1965. Three new synonymies are proposed: Spilogona impar (Stein, 1907) = Spilogona deflorata (Holmgren, 1872), Spilogona churchillensis Huckett, 1965 = Spilogona quinquesetosa (Schnabl, 1915), and Spilogona robusta Huckett, 1965 = Spilogona sordidipennis (Holmgren, 1883). The pictures of the new species are given and the male terminalia are figured. New faunistic data are given for some previously described species of Altai Spilogona.